Isolation and characterization of Bacillus velezensis: investigating its mechanisms as an effective biocontrol agent against Verticillium wilt in eggplants - Khattak, Arif Ali; Chen, Xiaoyuan; AbdAlamer, Iman Sabah; Tomah, Ali Athafah; Hussein, Rasha Abed; Al Farraj, Dunia A.; Elshikh, Mohamed Soliman; Afzal, Muhammad (Frontiers in Sustainable Food Systems, 2025)
Eggplant production in China is significantly impacted by Verticillium wilt caused by Verticillium dahliae, leading to substantial yield losses. This study was designed to investigate the potential of rhizobacterial species for the biocontrol of Verticillium wilt in eggplant. Among the 42 bacterial isolates tested, strain ARF4 demonstrated the strongest antagonistic effect by inhibiting V. dahliae growth by 84.49%, in addition to showing antifungal properties against four other plant pathogens. We found the strain ARF4 is closely related to Bacillus velezensis with high bootstrap values (100) through a phylogenetic tree based on 16S, rpoB, and gyrA gene sequences. The ARF4 produces important antifungal compounds such as chitinase, protease, β-glucosidase, and lipopeptide bacillomycin D, which contribute to its antifungal properties. The extracted lipopeptide of the ARF4 exhibited strong inhibition of conidial germination in V. dahliae. Scanning Electron Microscopy (SEM) showed that hyphae treated with the extracted lipopeptide exhibited considerable deformation. Transmission electron microscopy results revealed lysis of the cell walls and plasma membrane, a decreased inner cytoplasmic matrix and a number of mitochondria, and disintegration of internal organelles. Greenhouse trials demonstrated that eggplants treated with strain ARF4 experienced a significant disease severity reduction of 68.45%. This study offers B. velezensis ARF4 biological approach to Verticillium wilt control in eggplants as an alternative to chemical fungicides and contributes to sustainable agriculture practices.